A valoração da perícia psicológica por juízes de varas de família de Curitiba/PR e região metropolitana - Polak, Sibelle Hochsteiner do Amaral (2013)
This paper aims to present some national and international Forensic Psychology theory, as well the historical development and influences that inspired their origin. Displays the Family Forensic Psychology as a specialty area of Forensic Psychology, due the increasing demand of the psychologist in family courts, especially in evaluative activity. Finally, the text brings up legislative questions about brazilian Civil Procedure Code and resolutions of Federal Council of Psychology, involving the psychologist expert activity in the family courts.